2011
DOI: 10.1021/es200956p
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Genotoxicity, And Vascular Cell Adhesion Molecule Expression in Cells Exposed to Particulate Matter from Combustion of Conventional Diesel and Methyl Ester Biodiesel Blends

Abstract: Our aim was to compare hazards of particles from combustion of biodiesel blends and conventional diesel (D(100)) in old and improved engines. We determined DNA damage in A549 cells, mRNA levels of CCL2 and IL8 in THP-1 cells, and expression of ICAM-1 and VCAM-1 in human umbilical cord endothelial cells (HUVECs). Viability and production of reactive oxygen species (ROS) were investigated in all cell types. We collected particles from combustion of D(100) and 20% (w/w) blends of animal fat or rapeseed oil methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 27 publications
10
57
2
1
Order By: Relevance
“…The ROS production showed a bell-shaped concentration-effect relationship with a peak level at 12.5 µg/ml. This has also been observed in earlier investigations with CB and other types of particles with the same protocol [10], [11], [25], [26]. We show the results from the cell cultures that were exposed to 25 or 100 µg/ml, although these results were not included in the statistical analysis.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…The ROS production showed a bell-shaped concentration-effect relationship with a peak level at 12.5 µg/ml. This has also been observed in earlier investigations with CB and other types of particles with the same protocol [10], [11], [25], [26]. We show the results from the cell cultures that were exposed to 25 or 100 µg/ml, although these results were not included in the statistical analysis.…”
Section: Methodssupporting
confidence: 72%
“…The surface expression of ICAM-1 and VCAM-1 was measured with a modified ELISA procedure [10], [13], [26]. The expression of cell adhesion molecules were investigated in cultures with 2×10 4 HUVECs, 1.8×10 4 HUVEC +5×10 3 TPH-1a, 1×10 4 HUVECs +2.5×10 4 THP-1a, or 5×10 4 THP-1a in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…This was despite that carbon black induced intracellular ROS production in this experimental system and in other cell types also increased levels of oxidatively damaged DNA elevated mutant frequency with a spectrum related to ROS [36][37][38][39]. We have previously documented that combustionderived PM from different diesel fuels and engines, including one small car engine complying with the EU 2 standard, and standard reference material of PM from diesel combustion down to concentrations of 2.5 g/ml increased the level of SB and FPG-sensitive sites in lung (A549) epithelial cells [19,36,[39][40][41][42]. The number size distribution in the liquid suspension used for the ex vivo exposure study was not far from that found in chamber air.…”
Section: Discussionmentioning
confidence: 69%
“…The use of plant oils has been experimented with for a number of decades on a local basis, but is not extensively implemented as of yet. Limited evidence suggests that the exhausts from biofuel methyl esters of rape seed oil and soy oils have generated lesser emissions of volatile organic constituents and particle mass when compared to conventional DE (Hemmingsen et al, 2011; McDonald et al, 1997). However, it has been shown that atmospheric aging of biodiesel exhausts generates more ozone than aging of DE (Schröder et al, 1999).…”
Section: Introductionmentioning
confidence: 99%